Potential impact of vaginal microbicides on HIV risk among women with primary heterosexual partners. - McMahon, James M; Morrow, Kathleen M; Weeks, Margaret; Morrison-Beedy, Dianne; Coyle, Amanda (The Journal of the Association of Nurses in AIDS Care : JANAC, 2011)
This article explores the potential public health consequences of anti-HIV microbicide adoption among women in high-risk communities, using data from an exploratory study to illustrate key points. A brief quantitative survey was administered to 71 drug-using women with primary heterosexual partners in New York City. Only 37% of women reported recent condom use with a primary male partner. A total of 86% expressed willingness to use a microbicide with a primary partner. Among women using condoms, 50% believed they would decrease condom use if they started using a vaginal microbicide. Although overall condom use and intended condom migration was low among women with HIV-infected partners, universal promotion of microbicides could nonetheless lead to an increase in HIV risk among specific subgroups of women, indicating the importance of promoting continued condom use. Further research is needed to inform public policy decisions before the availability of the first commercial microbicide.
Keywords: Anti-Infective Agents, Local; Condoms; Female; HIV Infections; Humans; Male; Sexual Behavior; Sexual Partners; Vagina